2020
DOI: 10.1111/jcmm.15720
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA MEG3 inhibits M2 macrophage polarization by activating TRAF6 via microRNA‐223 down‐regulation in viral myocarditis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 49 publications
0
55
0
1
Order By: Relevance
“…We next sought to identify the MFG-E8-derived pathways responsible for chondrocyte senescence and macrophage reprogramming during OA. The NF-κB pathway is a well explored inflammatory pathway, which is over-activated in OA, exacerbating chondrocyte matrix degradation, synovial inflammation, and macrophage M1 polarization 21 , 22 . Excitingly, we found that MFG-E8 treatment rescued the phosphorylation of p65 NF-κB signaling, while neutralizing MFG-E8 significantly enhanced p65 phosphorylation both in cartilage and in synovium post OA surgery (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next sought to identify the MFG-E8-derived pathways responsible for chondrocyte senescence and macrophage reprogramming during OA. The NF-κB pathway is a well explored inflammatory pathway, which is over-activated in OA, exacerbating chondrocyte matrix degradation, synovial inflammation, and macrophage M1 polarization 21 , 22 . Excitingly, we found that MFG-E8 treatment rescued the phosphorylation of p65 NF-κB signaling, while neutralizing MFG-E8 significantly enhanced p65 phosphorylation both in cartilage and in synovium post OA surgery (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of miR-223 is regulated by three transcription factors, namely C/EBPα, PU.1, and NFI-A [ 48 ], and there is not any direct evidence that EP affects these transcription factors. On the other hand, EP may alter miR-223 expression through indirect mechanisms, such as long-non-coding RNAs (lncRNAs) and Nrf2 signaling pathway [ 49 , 50 , 51 , 52 ]. Some lncRNAs, such as GAS5, DLX6-AS1, and MEG3, have been reported to modulate miR-223 expression [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, EP may alter miR-223 expression through indirect mechanisms, such as long-non-coding RNAs (lncRNAs) and Nrf2 signaling pathway [ 49 , 50 , 51 , 52 ]. Some lncRNAs, such as GAS5, DLX6-AS1, and MEG3, have been reported to modulate miR-223 expression [ 49 , 50 , 51 ]. The Nrf2 signaling pathway is the main antioxidant signaling pathway under the stress condition, and overexpression of Nrf2 upregulates miR-223 expression [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA MEG3 was initially found to be a tumor suppressor that can inhibit the proliferation of tumor cells ( Benetatos et al, 2011 ), but has also been found recently to regulate pyroptosis ( Zhang Y. et al, 2018 ; Liang et al, 2020 ; Zou et al, 2020 ). Multiple studies have shown that MEG3 is involved in regulating inflammatory-response mechanisms in various diseases such as acute pancreatitis ( Xue et al, 2020 ), chronic obstructive pulmonary disease ( Lei et al, 2021 ), and ultraviolet skin injury ( Zhang et al, 2019 ). Disrupting the expression of MEG3 can reduce the production of inflammatory factors via various pathways.…”
Section: Discussionmentioning
confidence: 99%